Kekuatan Tarik Terhadap Beberapa Sudut Serat Pada Polimer Matrik Komposit Yang Berpenguat Serat Bambu Dengan Perlakuan Di Alkali Untuk Pengembangan Bodi Dan Rangka Kendaraan Elektrik - Purwanto, Hengki; Andary, Siti Rodiyah; Hartono, Hartono (Politeknik Negeri Jember, 2023)
Composite Matrix Polymer is a material formed by two or more combinations, Composite Matrix Polymer is a material consisting of two basic materials, namely matrix and fiber. For fibers it has elastic properties, and the best tensile strength, but also cannot be used against high temperatures, while matric itself has tenacious, soft properties.And it is also binding if it is dry or has reached freezing. This research is to determine the material with natural fibers, namely bamboo fibers that have been processed to such an extent as to realize or entrepreneurial opportunities in the field of body and electric vehicle frames. For this reason, we made this research.To determine the effect of variations in the fibrous angles of composite matrix polymers with angles (0°), (-45°, 45°), and (-45°, 0°, 45°), With bamboo fiber reinforcement for the addition of bamboo fiber variations and with Alkaline treatment at the ratio of NaOH solution levels of 5%, 10%, and 15%, thus to carry out the addition of alkaline treatmentThis study uses experimental methods, and can determine the influence of angular variations, composite matrix polymer fibers with fiber angles (0°), (-45°, 45°), and (-45°, 0°, 45°) reinforced bamboo fibers, with the influence of variations in alkaline dosing of bamboo fibers and the ratio of NaOH solution levels of 5%, 10%, and 15% on the tensile strength of the material.The result of the tests that we have done, is the use of a good 5% alkaline content, a 5% alkaline solution content gets the best fiber speciment form than a 10% and 15% alkaline solution. And the lowest result is an alkaline content of NaOH 15%. While the best result of angle variation is the angle variation (-45°, 0°, 45°) and the lowest is the angle variation (0°). Which will then be used as a method for learning or practicum modules at the Jember State Polytechnic.